Accountants' personality types and their commitment to organization and profession* - ARANYA, NISSIM; WHEELER, JOHN T. (Contemporary Accounting Research, 1986)
This study, based on Holland's theory, examines the relationship between accountants' personality types and their commitment to work in various occupational settings and organizational levels. Empirical evidence on this subject may have useful implications for personnel selection and job design in public accounting firms as well as in industry. The results show that conventional and enterprising types were the most frequent among the 1206 Canadian CAs and 810 California CPAs who participated in the study. In addition, a larger proportion of sole practitioners and partners in small firms tend to be of the conventional type, whereas the enterprising type comprises the largest proportion of partners in large firms. Canonical correlations indicate that accountants' commitment to both profession and organization is essentially related to their scores as conventional and enterprising types. Résumé. Fondée sur la théorie de Holland, cette étude porte sur les relations entre les types de personnalités de comptables et leur dévouement au travail, à l'intérieur de milieux de travail et de niveaux organisationnels divers. Les informations de nature empirique issues de cette question peuvent possiblement influencer les activités de sélection de personnel et de conception de tâches au sein des cabinets d'experts‐comptables et de l'industrie. Les résultats indiquent une fréquence élevée des types de personnalité conformiste et entreprenant parmi les 1206 c.a. canadiens et les 810 c.p.a. de Californie ayant pris part à l'étude. De plus, une forte proportion de practiciens autonomes et d'associés de petits cabinets se trouve dans le type de personnalité conformiste, tandis que le type entreprenant est composé surtout d'associés de grands cabinets. Des corrélations canoniques montrent que le dévouement des comptables à l'organisation et à la profession est surtout relié à leurs scores de types conformiste et entreprenant.